2016
DOI: 10.1007/978-3-319-43488-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Synchronously Imitate Gestures Using Entrainment Effect

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In other recent examples, using a very simple neural network providing minimal sensorimotor adaptation capabilities to the robot, unintentional motor coordination could emerge during an imitation game (of a simple gesture) with a human (Hasnain et al 2012;. An extension of this work demonstrated that a robot could quickly and "online" learn more complex gestures and synchronize its behavior to the human partner based on the same sensorimotor approach (Ansermin et al 2016).…”
Section: Ludovic Marin a And Ghiles Mostafaoui B Amentioning
confidence: 74%
“…In other recent examples, using a very simple neural network providing minimal sensorimotor adaptation capabilities to the robot, unintentional motor coordination could emerge during an imitation game (of a simple gesture) with a human (Hasnain et al 2012;. An extension of this work demonstrated that a robot could quickly and "online" learn more complex gestures and synchronize its behavior to the human partner based on the same sensorimotor approach (Ansermin et al 2016).…”
Section: Ludovic Marin a And Ghiles Mostafaoui B Amentioning
confidence: 74%
“…Closer to this work, [10] introduced a model designed to reproduce rhythmic arm movements with the NAO robot. A reservoir of oscillators provides one with a close frequency and while the oscillator can be slightly entrained during the interaction, the oscillators do not retain the frequency, going back to their original properties right afterwards.…”
Section: Related Workmentioning
confidence: 99%
“…In other recent examples, using a very simple neural network providing minimal sensorimotor adaptation capabilities to the robot, unintentional motor coordination could emerge during an imitation game (of a simple gesture) with a human (Hasnain et al 2012; 2013). An extension of this work demonstrated that a robot could quickly and “online” learn more complex gestures and synchronize its behavior to the human partner based on the same sensorimotor approach (Ansermin et al 2016).…”
mentioning
confidence: 93%